Objective Truth and Contentiousness in Criminal Procedure: Confrontation and Mutual Addition - Ryabkov E. M. (Vestnik Omskoj Ûridičeskoj Akademii, 2014)
The article deals with one of the disputable issues of the modern theory of criminal court proceedings – truth as the aim of proof. The proposals on legislation improvement in this sphere are analyzed